Micro scale environmental characteristics and fear of crime / Eylem Akman Cinar and Ebru Cubukcu - Cubukcu, Ebru; Akman Cinar, Eylem (Faculty of Architecture, Planning and Surveying, 2013)
This study investigated the relation between crime, fear, and micro level physical environmental features: physical incivilities, places that afford concealment (or refuge), limited prospect, and blocked escape. Low and high crime streets in Istanbul, Turkey was determined. Then 68 streets were selected via cluster random sampling and evaluated by two investigators at the site and by 127 people via photographs for perceived safety, upkeep (as an indicator of physical incivilities) the extent to which they afford wide vista (prospect) and easy escape and concealment opportunities, the density and height of trees, shrubs, and walls. Results supported the theory and the findings of previous empirical studies.